2021
DOI: 10.21836/pem20210301
|View full text |Cite
|
Sign up to set email alerts
|

Results of 654 trans-pars plana vitrectomies of equine eyes with recurrent uveitis – follow-up until 18 years after surgery

Abstract: Results of 654 trans-pars plana vitrectomies of equine eyes with recurrent uveitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…In European horses without a leopard coat pattern, the most effective method to prevent further episodes of uveitis and thereby preserve vision is vitrectomy [10,[18][19][20][21]. After a properly performed vitrectomy, which has been routinely performed for more than 30 years in horses with ERU, the control of inflammation is seen in 90-97% of horses [10,13,[21][22][23][24]. By contrast, uveitis in horses with a leopard coat pattern manifests differently.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In European horses without a leopard coat pattern, the most effective method to prevent further episodes of uveitis and thereby preserve vision is vitrectomy [10,[18][19][20][21]. After a properly performed vitrectomy, which has been routinely performed for more than 30 years in horses with ERU, the control of inflammation is seen in 90-97% of horses [10,13,[21][22][23][24]. By contrast, uveitis in horses with a leopard coat pattern manifests differently.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have suggested an association between leptospiral infection and ERU [26][27][28][29][30][31]. For example, anti-Leptospira antibodies are regularly detected in vitreous material obtained during vitrectomies [13,15,21,[32][33][34][35][36][37][38][39][40][41]. These antibodies are detected using the micro agglutination test (MAT), and various enzyme-linked immunosorbent assays (ELISA) [42,43].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations